Intervening spaces : respatialisation and the body - Prowse, Nicole (At the interface/probing the boundaries, 2018)
This book examines the interconnectedness between bodies, time and space - the oscillating and at times political impact that occurs when bodies and space engage in non-conventional ways. Bodies intervene with space, creating place. Likewise, space can reconceptualise notions of the subject-body. Such respatialisation does not occur in a temporal vacuum. The moment can be more significant than a millennia in producing new ways to see corporeal connections with space. Drawing on theorists as diverse as Foucault, Deleuze, Guattari, Heidegger, Merleau-Ponty, Lefebvre and Grosz, temporal and spatial dichotomies are dissolved, disrupted and interrupted via interventions-revealing new ways of inhabiting space. The volume crosses disciplines contributing to the fields of Sociology, Literature, Performance Arts, Visual Arts, Architecture and Urban Design.0.